I'm having difficulty with this old qualifying exam problem. Suppose we have a sequence of independent R.V's $\{X_n\}_{n\in\mathbb{N}}$ satisfying,

$$ \mathbb{P}(X_n = \pm n^2) = \frac{1}{12n^2}, \;\;\;\; \mathbb{P}(X_n = \pm n) = \frac{1}{12}, \;\;\;\; \mathbb{P}(X_n = 0) = 1 - \frac{1}{6} - \frac{1}{6n^2}$$

I managed to show that the Lindeberg condition does not hold. However, the problem states that the sequence $\frac{S_n}{b_n}$ still converges in distribution to a standard normal, where,

$$ S_n = \sum\limits_{k=1}^nX_k, \;\;\; b_n^2 = \frac{n(n+1)(2n+1)}{18} $$

Is there any cheeky way to show this? I tried using characteristic functions, but I feel like this method would be too inefficient on a timed exam.

EDIT: I consulted with the graduate director and he told me that there was a typo in the question. The question was actually taken from Chung's "A Course in Probability Theory" text (Section 7.2, Exercise 10). The correct problem states:

A CLT may well hold with a different sequence of constants $b_n$. Prove that Lindberg's condition is not satisfied. Nonetheless, if we take $b_n^2 = n^3/18$, then $S_n/b_n$ converges in dist. to the standard normal. The point is that abnormally large values may not count! Hint: Truncate out the abnormal value


I think there is somthing off with the problem. Let's recall the following well-known statement:

Let $(X_n)_{n \in \mathbb{N}}$ be a sequence of real-valued independent random variables such that $\mathbb{E}(X_k)=0$ and $\sigma_k^2 = \mathbb{E}(X_k^2)>0$. Set $s_n^2 := \sum_{k=1}^n \sigma_k^2$. If $(X_n)_{n \in \mathbb{N}}$ satisfies the Feller condition $$\lim_{n \to \infty} \max_{1 \leq k \leq n} \frac{\sigma_k^2}{s_n^2} = 0, \tag{F}$$ then the following two statements are equivalent:

  1. $\frac{1}{s_n} (X_1+\ldots+X_n)$ converges in distribution to a standard Gaussian random variable.
  2. The Lindeberg condition holds: $$\forall \epsilon>0: \quad \lim_{n \to \infty} \frac{1}{s_n^2} \sum_{k=1}^n \int_{|X_k|>\epsilon s_k} |X_k|^2 \, d\mathbb{P}=0. \tag{L}$$

In the given example, we have

$$\sigma_k^2 = \mathbb{E}(X_k^2) = k^4 \mathbb{P}(|X_k| = k^2) + k^2 \mathbb{P}(|X_k| = k) = \frac{1}{3} k^2$$

and so

$$s_n^2 = \sum_{k=1}^n \sigma_k^2 = \frac{1}{18} n (n+1) (2n+1).$$

In particular, we find

$$\max_{k \leq n} \frac{\sigma_k^2}{s_n^2} \leq 6 \frac{n^2}{n (n+1)(2n+1)} \xrightarrow[]{n \to \infty} 0,$$

i.e. the Feller condition (F) holds. By the above theorem, this means that the CLT holds if, and only if, the Lindeberg condition (L) is satisfied. However, $s_k \approx k^{3/2}$ for large $k$, and therefore

$$\int_{|X_k|>\epsilon s_k} |X_k|^2 \, d\mathbb{P} = \int_{|X_k| = k^2} k^4 \, d\mathbb{P} = \frac{1}{6}k^2$$

for large $k$ implying that

$$\frac{1}{s_n^2} \sum_{k=1}^n \int_{|X_k|>\epsilon s_k} |X_k|^2 \, d\mathbb{P}\approx \frac{3}{n(n+1) (2n+1)} \sum_{k=1}^n k^2 = \frac{1}{18}$$

does not converge to $0$ as $n \to \infty$; this shows that (L) does not hold, and consequently (CLT) cannot hold true.

  • $\begingroup$ Thank you. Apparently there was a problem with the question. The CLT holds for the sequence $n^3/18$ and not $n(n+1)(2n+1)/18$. $\endgroup$ – Flowsnake Jan 18 '18 at 22:00
  • $\begingroup$ If we replace $X_k$ by $\sigma X_k$, then wouldn't the $\sigma$ cancel out in the ratio $\frac{1}{s_n}\sum\limits_{k=1}^nX_k$? Then we would be back to square one. I'm still not sure why the ratio cannot converge to any $N(0, \sigma^2)$. $\endgroup$ – Flowsnake Jan 19 '18 at 20:55
  • $\begingroup$ @Flowsnake Ah you are right; it would cancel out. Something still feel off to me, but it might well be that there is an error in my logic. I'll think about it $\endgroup$ – saz Jan 19 '18 at 21:11

Adding to what saz said, I found similar problems from a different approach. I took your idea of characteristic functions (although by simplicity reduced to moment generating functions). For each $X_n$ we have $$M_{X_n}(t)=\frac56-\frac1{6n^2}+(e^{nt}+e^{-nt})\frac1{12}+(e^{n^2t}+e^{-n^2t})\frac1{12n^2}.$$

Then for $S_n$, since the $X_1,\ldots,X_n$ are independent $$M_{S_n}(t)=\prod_{k=1}^n M_{X_k}(t)=\prod_{k=1}^n \left(\frac56-\frac1{6k^2}+(e^{kt}+e^{-kt})\frac1{12}+(e^{k^2t}+e^{-k^2t})\frac1{12k^2} \right).$$

Finally, if we define $Z_n=\tfrac{S_n}{b_n}$, then

$$M_{Z_n}(t)=M_{S_n}\left(\frac{t}{b_n}\right)=\prod_{k=1}^n \left(\frac56-\frac1{6k^2}+(e^{kt/b_n}+e^{-kt/b_n})\frac1{12}+(e^{k^2t/b_n}+e^{-k^2t/b_n})\frac1{12k^2} \right).$$

Now, since MGF of $Z_n$ are well defined in a neighborhood of $t=0$, it's a theorem that $$Z_n \to N(0,1) \, (\mathcal D) \quad \iff \quad M_{Z_n}(t) \to e^{\tfrac{t^2}2},$$ or more generally $$Z_n \to Y \, (\mathcal D) \quad \iff \quad M_{Z_n}(t) \to M_Y(t).$$

Since the expression of $Z_n$ is not even close to "friendly", I've estimated it's values and found out that (apparently) $$M_{Z_n}(t)\to \infty, \, t\neq 0.$$

This implies that $Z_n$ does not converge in distribution to a distribution with a well defined MGF, and certainly, that it does not converge to a normal distribution.

  • $\begingroup$ Thank you. Apparently there was a problem with the question. The CLT holds for the sequence $n^3/18$ and not $n(n+1)(2n+1)/18$. $\endgroup$ – Flowsnake Jan 18 '18 at 22:01

I believe I've gotten to a solution. Following the hint, define the truncated R.V's, $Y_j = X_jI\{|X_j| \leq j\}$. Then,

$$ \sum\limits_{j=1}^\infty\mathbb{P}(X_j \neq Y_j) = \sum\limits_{j=1}^\infty\mathbb{P}(X_j = \pm j^2) = \sum\limits_{j=1}^\infty\frac{1}{6j^2} < \infty $$

By Borel-Cantelli, $\mathbb{P}(X_j \neq Y_j \;\; i.o.) = 0$, i.e. $\{X_j \neq Y_j\}_{j\in\mathbb{N}}$ can only occur finitely many times. Thus, $S_n^* = \sum\limits_{j=1}^nY_j$ and $S_n = \sum\limits_{j=1}^nX_j$ have the same asymptotic distribution. One can show that the Lindeberg condition applied to $\{Y_j\}_{j\in\mathbb{N}}$ does hold. Thus,

$$ S_n/b_n \sim S_n^*/b_n \xrightarrow{n\rightarrow\infty} N(0,1) $$

where $b_n^2 = \sum\limits_{j=1}^n\mathbb{E}[Y_j^2] = \sum\limits_{j=1}^n\frac{j^2}{6} \sim \frac{n^3}{18}$. The notation $\sim$ is taken to mean "asymptotically equal".

EDIT: To justify why $S_n/b_n$ and $S_n^*/b_n$ have the same asymptotic distribution, I used the following results from Chung's "A Course in Probability Theory".

DEFINITION. Two sequences of R.V.'s $\{X_n\}$ and $\{Y_n\}$ are said to be equivalent iff $$\sum\limits_n\mathbb{P}(X_n \neq Y_n) < \infty$$ Theorem. If $\{X_n\}$ and $\{Y_n\}$ are equivalent, then, $$ \sum\limits_{n}(X_n - Y_n) $$ converges almosut surely. Moreover if $a_n$ is a monotonic sequence diverging to $+\infty$, then, $$ \frac{1}{a_n}\sum\limits_{j=1}^n(X_j - Y_j) \xrightarrow{n\rightarrow\infty} 0 $$ almost surely.

  • $\begingroup$ How exactly do you justify that $$S_n/b_n \to N(0,1) \iff S_n^*/b_n \to N(0,1)$$ ...? $\endgroup$ – saz Jan 19 '18 at 7:58
  • $\begingroup$ Please see my edit. I referred to the textbook that the problem was taken from. $\endgroup$ – Flowsnake Jan 19 '18 at 20:52
  • $\begingroup$ I'm well aware of the result about the equivalence of sequences. What was bothering me is that you are mixing almost sure convergence and convergence in distribution... but after I have thought once more about it, I think that your reasoning is fine. $\endgroup$ – saz Jan 20 '18 at 9:49

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.